(untitled) (Abhat Journal, 2024)
One of the greatest goals of this research is to clarify the conditions of judges, based on the two revelations. As a result of clarifying their conditions, we can deduce the effects resulting from judicial corruption in all its types and levels, from political to economic, and ending with social corruption; in order to reach solutions that limit its effectiveness or end it, following the path of investigators from among the people of knowledge by extrapolating the texts and linking them to the reality lived today, and projecting them in a way that is consistent with rational, objective consideration. Likewise, one of its most important goals is to direct the liberation of that divine light from the abhorrent restrictions that have befallen it - corruption - which are not fundamental to its essence; so that it is able to make any decision without any pressure. I do not mean by liberation the separation from those lofty meanings, and emptying society of morals and values, which are like the internal power and authority that controls the unruly soul from falling into what may be considered ugly, but rather the liberation of its origin is servitude to God, Lord of the Worlds, and with controls that define its features; So that we do not live in barbarism and chaos by giving free rein to the mischief-makers and corruptors without accountability, no matter how high their positions are, and by demonstrating that no one is exempt from accountability.